2007
DOI: 10.1007/s11237-007-0024-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of polyoxometallate complexes of nickel and copper on the rate of their heterophase reaction with ammonia

Abstract: It was established that the compounds formed by the cations in amine complexes of nickel(II) and copper (II) and the anions of polyoxometallates are capable of reacting stoichiometrically with gaseous ammonia when in the hydrated state. Some of the studied compounds are characterized by high sorption capacity (up to 40 molecules of adsorbate to a formula unit of the complex) and exhibit selectivity in the sorption of ammonia in the presence of water vapor.The anions of polyoxometallates (POM) are convenient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…The letter "a" denotes dehydrated samples of the corresponding compounds; a the amount of bound adsorbate molecules per formula unit of the starting crystal solvate at saturation, the amount of irreversibly adsorbed alcohol molecules is given in parentheses; b the amount of additional water molecules adsorbed by the crystal solvate at 100% relative humidity according to our previous data [12]; c samples "melt" under the experimental conditions; d the amount of EtOH molecules in addition to the crystal solvates.…”
Section: Notementioning
confidence: 99%
See 4 more Smart Citations
“…The letter "a" denotes dehydrated samples of the corresponding compounds; a the amount of bound adsorbate molecules per formula unit of the starting crystal solvate at saturation, the amount of irreversibly adsorbed alcohol molecules is given in parentheses; b the amount of additional water molecules adsorbed by the crystal solvate at 100% relative humidity according to our previous data [12]; c samples "melt" under the experimental conditions; d the amount of EtOH molecules in addition to the crystal solvates.…”
Section: Notementioning
confidence: 99%
“…As in previous cases, [M(L)] x [POM] y compounds where M is Cu 2+ or Ni 2+ , L is the tetradentate acyclic tetramine 1,9-diamino-3,7-diazononane (L 1 ) or macrocyclic ligand 2,4-diamino-1,3,5-triazin-6-yl-[3-(1,3,5,8,12-pentaazacyclotetradecane)] (L 2 ). The synthesis of the complex was carried out in water-alcohol media in accord with our previous procedures [11,12]. The elemental analysis data indicated that these compounds differ in the ratio of the cationic and anionic components (1 : 1 for 1, 2, and 11, 2 : 1 for 4, 6, and 7, 3 : 2 for 5, 8, 9, and 10) or contain two types of cations (3) ( Unfortunately, the low solubility of the compounds hinders the formation of monocrystals suitable for X-ray diffraction structural analysis.…”
Section: Notementioning
confidence: 99%
See 3 more Smart Citations